Desenvolvimento de um protótipo de controle de nível baseado em arduino: uma abordagem utilizando sensor ultrassônico - Reis, Lara Elisa Pereira (2024)
Standardizing processes in the food industry ensures quality and safety. While large industries use automation for level control, small businesses face challenges due to limited financial resources. In this context, developing low-cost solutions for level control is relevant. This study developed a low-cost liquid level monitoring and control system using an ultrasonic sensor and On-Off control, based on an Arduino microcontroller. The prototype was assembled and electronic devices were installed. A code was developed for sensor calibration and subsequently for implementing the calibration curve, achieving a coefficient of determination (R²) of 0.9719. System validation confirmed its efficiency, with the system automatically adjusting the water level according to user-defined limits and showing an average error of -4.7% ± 7.2% during operation. Besides being economically accessible, the prototype proved suitable for various applications, although it may not be appropriate for systems requiring high precision.